DESIGN ANALYSIS OF TRACTION MOTOR AIR COOLING DUCT OF TRAXX ASIA DIESEL ELECTRIC LOCOMOTIVE - FARIS NAUFAL AUSTEN (NIM : 13107001); Pembimbing Utama : I Made Astina, Ph.D.; Pembimbing Pe, MUHAMAD
In 2012, PT INKA plans to make diesel-electric locomotive designed by PT INKA itself. An important component in diesel-electric locomotive is a traction motor. In order to operate safely, an effective traction motor coolingsystem must be planned. In this research, several alternatives of cooling air ducts will be studied to get the duct with small pressure losses and suitable with the locomotive system. Traction motor cooling in locomotive is conducted by flowing ambient air into the traction motor. Minimum requirement for the air flow is 1,7 m3/s to prevent overheating during its operation. The air flow for each traction motor should be relatively equal. Allowable tolerance of the difference is 5%, that of 1/3 times of the inlet air flow. In this case study, design analysis process is carried by making out a few models and numerical calculations are conducted with CFD FLUENT to get an air duct that has minimum pressure losses. Analytical validation, manufacturability analysis, and wall thickness analysis are also performed to obtain the best result. Six models are proposed, i.e. models 1 through 4 have different branches size, whereas models 5 and 6 has a modified form of curves. The analysis result shows that model 6 is the best model. For this model, minimum specification of blower is that the pressure is 4300 Pa and the air flow is 5.26 m3/s. Wall thickness of the air duct without reinforcement is varying from 5 mm at the beginning of branch to 1.5 mm at nearby the air duct outlet.